Fragmented Narrative Technique as A Depiction of Trauma in Alice Munro's Dimensions - Hayati, Dzikrika Rahmatu (Journal of Language, Literature and Teaching, 2024)
This study examines the use of narrative techniques in depicting trauma and fragmented memories in the short story